REER: Robust and Energy Efficient Multipath Routing Protocol for Wireless Sensor Networks - Yahya, B.; Ben-Othman, J. (GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference, 2009)
Wireless Sensor Networks (WSNs) are subject to node failures because of energy constraints, as well nodes can be added to or removed from the network upon application demands, resulting in unpredictable topology changes. Furthermore, due to limited transmission range of wireless sensor nodes, multiple hops are usually needed for a node to exchange information with other nodes or sink node(s). This makes the design of routing protocols in such networks a challenging task. In all proposed single path routing schemes a periodic low-rate flooding of data is required to recover from path failures, which causes consumption of scarce resources of the sensor node. Thus multipath routing schemes is an optimal alternative to maximize the network lifetime. Multipath routing schemes distribute the traffic across multiple paths instead of routing all the traffic along a single path, which spreads consumed energy evenly across the nodes within the network, potentially resulting in longer lifetimes. In this paper, we propose a robust and energy efficient multipath routing protocol (shortly abbreviated as REER). REER uses the residual energy, node available buffer size, and Signal-to-Noise Ratio (SNR) to predict the best next hop through the paths construction phase. REER examines two methods of traffic allocation; the first method uses a single path among the discovered paths to transfer the data message, when this path cost falls bellow a certain threshold, it then switches to the next alternative path. The second method is to split up the transmitted message into number of segments of equal size, add XOR-based error correction codes, and then transmit it across multiple paths simultaneously to increase the probability that an essential portion of the packet is received at the destination without incurring excessive delay. Through computer simulation, we evaluate and study the performance of our routing protocol and compare it with other protocols. Simulation results show that our protocol achieves more energy savings, lower average delay and higher packet delivery ratio than other protocols.